Community contacts and participation of teachers in four towns in Zambales - Firme, Tito F. 1895- ([Quezon City University of the Philippines], 1955)
This survey lies in the general field of teachers and community relations. It proposes to locate the factors and extent of community contacts and participation of teachers in the community- in which they work and live. It is a survey on the out-of-school life of teachers in which they generally get in contact with the community through three major areas: professional services, citizenship activities and leisure time pursuits.
Bibliography: l. 141-143.
Thesis (M.Ed.)--University of the Philippines, 1955
Vita
Typewritten
Keywords: Community and school; Education -- Zambales